Strategi Dalam Meningkatkan Kinerja Karyawan Kantor Depan di The Royal Santrian Luxury Beach Villas Pada Masa Pandemi - Ni Ketut Sekarti; Komang Dea Ariska Febriyanti; I Made Sucipta Adnyana (Journal of Hospitality Accommodation Management (JHAM), 2023)
The purpose of this research is to find out how the strategy to improve the performance of front office employees during the pandemic. This research is motivated by a decrease in the performance of front office employees during the pandemic period in the 2020-2021 period by showing that front office employees are not enthusiastic about work, make mistakes in doing work. This research uses a qualitative descriptive method by describing existing phenomena that pay more attention to the characteristics, quality, and interrelationships between activities. Data collection techniques used in this study were interviews with informant concerned with strategies to improve performance, namely Front Office Manager, Human Resources Manager, and one of the Receptionists at The Royal Santrian Luxury Beach Villas, and documentation study. The results showed that the strategy in improving the performance of front office employees in four indicators, namely discrimination, rewards, training and development, and communication has not been fully implemented properly.